English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

7 answers

The first step to solving this problem is remembering slope-intercept form: y = mx + b, where m is the slope of the line and b is the y-intercept.

First we need to find the slope.
Slope = m = rise/run = (y2 - y1) / (x2 - x1)
= (-5 - 1) / (-2 - (-3)
= (-6) / (-2+3)
= -6 / 1
= -6

Putting this into the form of y = mx + b we have: y = -6x + b.
All that remains is determining the y-intercept. The easiest way to do this is put the values (x, y) from one of your points back into the equation. Arbitrarily selecting (-3, 1) we get the equation:

1 = -6(-3) + b
1 = 18 + b
-17 = b

Finally, put b into the slope-intercept form of your equation:
y = -6x - 17

2006-12-01 10:15:27 · answer #1 · answered by n.callaway 1 · 0 0

The slope of the line between those factors is m = (y2 - y1) / (x2 - x1) = (a million-(-5)) / (-2-3) = 6/-5= -6/5 Slope intercept style is y - y1 = m(x - x1) y - (-5) = (-6/5)(x - 3) y + 5 = -6x/5 + 18/5 y = -6x/5 - 7/5

2016-12-10 20:01:46 · answer #2 · answered by ? 4 · 0 0

Reminder that slope is equal to (y2 - y1)/(x2 - x1).

Therefore,

m = (1 - (-5))/(-3 - (-2)) = 6/-1 = -6

To calculate the equation of the line, use the "slope = slope" method, with one of the points.

(y - 1) / (x - (-3)) = -6
(y - 1)/(x + 3) = -6
y - 1 = -6(x+3)
y - 1 = -6x - 18
y = -6x + 17

2006-12-01 09:43:25 · answer #3 · answered by Puggy 7 · 0 0

slope = m = (y2- y1) / (x2 - x1) slope equation

m = (-5 - 1) / (-2 - (-3)) = -6 / 1 = -6

next we use the point-slope form because we have a slope (m= -6) and a point (actually 2 to chose from)

y - y1 = m(x - x1)

y - 1 = (-6) (x -(-3))
y - 1 = -6(x + 3)
y - 1 = -6x - 18
+1 to both sides

y = -6x - 17

2006-12-01 09:38:48 · answer #4 · answered by ledezmajr 3 · 1 0

m(slope)= (-5-1)/(-2-(-3)
= -6

y=mx+b
sub in the correct variables
1=-6(-3)+b
solve for b:
b=-17
y=-6x-17

2006-12-01 09:40:59 · answer #5 · answered by acurran081789 1 · 0 0

Use a TI-83 or TI-84 calculator.....

2006-12-01 09:37:18 · answer #6 · answered by viperprincess07 2 · 0 0

m=(1--5)/(-3--2)=6/-1=-6
y=-6x+b
1=-6*-3+b
1=18+b
b=-17
y=-6x-17

2006-12-01 10:06:38 · answer #7 · answered by yupchagee 7 · 0 0

fedest.com, questions and answers